Discourse in Billboard Woman of The Decade award: an actantial analysis - Max, Jonathan Irene Sartika Dewi; Sudirman, Eka Pratiwi; Rahayu, Famala Eka Sanhadi; Nugroho, Bayu Aji (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2023)
Examining how the meaning is made needs not only a description of how grammatical choices are categorized and explain the most used categories to directly grasp implied meaning but to see how humans use language to place narrative elements to configure the body of a story. The speech delivered by Taylor Swift as she entitled Woman of the Decade by Billboard music award in 2019 used to demonstrate this scheme. Halliday’s transitivity system is applied to see how it first works to realize the narrative that is directed by the actantial roles as suggested by Greimas’s narratology which then develops a discourse. Linguistic evidence in this speech is found to support the six actant roles filling three axes. The axis of desire puts the speaker herself as the subject pursuing the right to own and control her art in music with fair revenue flow in an inclusive work environment as the object. The axis of communication puts her experience, fans, and music as the sender to the quest that benefits the receivers who are the female singers and the younger generation. The axis of power insists on persistence, technology, social media, and peer support as the enabling aspect overcoming the opponent which are detractors, old scheme contracts in unregulated private equity, toxic male privilege, and harsh criticism led by impossible standards.